Outcome of Liver Transplant Recipients With Revascularized Coronary Artery Disease: A Comparative Analysis With and Without Cardiovascular Risk Factors - Satapathy, Sanjaya K. (Transplantation, 2017)
BACKGROUND: Coronary artery disease (CAD) is a significant problem during evaluation for liver transplantation (LT). We aim to assess survival in LT recipients based on presence, severity, extent of CAD, and cardiac events within 90 days of LT. METHODS: Eighty-seven LT recipients with history of pre-LT angiogram (December 2005 to December 2012) were compared with 2 control groups without prior angiogram, 72 LT recipients matched for cardiovascular risk factors (control group I), and 119 consecutive LT recipients without any CV risk factors (control group II). CAD was assessed by (1) vessel score (≥50% reduction in luminal diameter), and (2) Extent score (Reardon scoring system). RESULTS: Of the 87 LT recipients (study group), 58 (66.7%) had none or less than 50% stenosis, 29 (33.3%) had obstructive CAD (≥50% stenosis), 7 (8%) with single-vessel disease, and 22 (25.3%) with multivessel disease. In the study group, irrespective of prerevascularization severity of CAD (P = 0.357), number of segments involved (0, 1-2, > 2 segments, P = 0.304) and extent of CAD based on Reardon score (0, 1-9, >10, P = 0.224), comparable posttransplant survival was noted. Overall, patient survival in the revascularized CAD group was comparable to angiogram group without obstructive CAD, and both control group I and control group II (P = 0.184, Log Rank). Postoperative cardiac events within 90 days of LT predicted poor survival in study group as well as control groups. CONCLUSIONS: Severity or extent of CAD does not impact post-LT survival, if appropriately revascularized. Early postoperative cardiac events are associated with inferior survival in LT recipients, irrespective of underlying CAD.